PELATIHAN PEMBUATAN ARTIKEL DAN PENGGUNAAN AI UNTUK KENAIKAN JABATAN FUNGSIONAL GURU KB -TK ANANDA SURABAYA - Wisnu Kristanto; Alfina Citrasukmawati; Suhartini Nurul Azminah (Jurnal Terapan Abdimas, 2025)
Abstract. The task of teachers is not only in the learning process, but also in sustainable professional development, where the lack of this development also has an impact on credit scores and hampered teachers' careers. The main obstacle to collecting credit scores is the creation of scientific work or innovative work. The aim of this community service is to improve the ability to write scientific articles among kindergarten teachers which is carried out through material presentation activities and practice of looking for ideas based on problems in class, looking for scientific articles according to problems, creating solutions to problems in class, making paraphrases, and writing lists. library according to reference articles. Indicators of success in this service can be seen from attendance, enthusiasm in asking questions, and increasing teacher ability, where it can be seen that attendance reaches a percentage of 100%, enthusiasm in asking questions reaches a percentage of 75%, and the increase in teacher ability reaches 100%. The conclusion of this activity is that the community service that has been carried out has had a positive impact and there has been an increase in the ability to write scientific articles for Ananda KB-TK teachers.   Abstrak. Tugas guru tidak hanya pada proses pembelajaran, akan tetapi juga pada pengembangan keprofesian berkelanjutan, di mana minimnya pengembangan ini juga berdampak pada angka kredit dan karir guru yang terhambat, kendala utama dari pengumpulan angka kredit ini adalah pembuatan karya ilmiah atau karya inovatif. Tujuan dilakukan pengabdian masyarakat ini adalah meningkatkan kemampuan dalam menulis artikel ilmiah di kalangan guru TK yang dilakukan melalui kegiatan pemaparan materi dan praktik mencari ide berdasarkan permasalahan di kelas, mencari artikel ilmiah sesuai permasalahan, membuat solusi dari permasalahan di kelas, membuat parafrase, dan menulis daftar pustaka sesuai artikel rujukan. Indikator keberhasilan dalam pengabdian ini dapat dilihat dari kehadiran, antusiasme dalam bertanya, dan peningkatan kemampuan guru di mana dapat dilihat bahwa kehadiran mencapai persentase 100%, antusiasme dalam bertanya mencapai persentase 75%, dan peningkatan kemampuan guru mencapai 100%. Kesimpulan dari kegiatan ini adalah pengabdian masyarakat yang telah dilakukan memiliki dampak positif dan terjadi peningkatan kemampuan dalam menulis artikel ilmiah bagi guru KB-TK Ananda.